Quantitation of Floxuridine in K2 EDTA Rat Plasma using HPLC Coupled with Tandem Mass Spectrometry - Nageswara Rao, R.; Jagannath Patro, V.; Tripathy, N.K. (Asian Journal of Chemistry, 2012)
A rapid, sensitive and specific method based on high performance liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) detection with electro spray ionization in negative ionization mode has been developed for the determination of floxuridine in K2 EDTA rat plasma. Sample preparation involved liquid-liquid extraction with ethyl acetate. Chromatographic separation was performed on Agilent Eclipse XDB column (C18 150 × 4.6 mm 5 μ), with a mobile phase consisting of methanol and 1 mM ammonium acetate at a flow rate of 0.4 mL/ min. The analytes were then detected by monitoring the transitions m/z 245.2-155.1 for floxuridine and m/z 321.5-143.9 for 5-bromouridine(IS) using API-4000 LC-MS/MS system (applied biosystems). Calibration curves were linear within the range of 0.050 to 50.00 ng/mL. The lower limit of quantitation (LLOQ) was 0.050 ng/mL. The method has been fully validated in rat plasma. This method can be successfully applied to the pharmacokinetic study sample analysis.